2021
DOI: 10.1021/acsami.1c13651
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Gamma-Ray Irradiation Effects on Carbon Nanotube Top-Gated Field-Effect Transistors

Abstract: Carbon nanotube (CNT) field-effect transistors (FETs) and integrated circuits (ICs) have been predicted and demonstrated to be some of the most promising candidates for radiation-hardened electronics. The studies mainly focused on the radiation response of the whole transistors, and experiments or analyses to reveal the detailed radiation responses of different components of the FET were absent. Here, we use a controllable experimental method to decouple the total ionizing dose (TID) radiation effects on diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…However, for irradiated samples, situation is quite different because samples suffer many chemical and physical changes because of radiation-induced free radicals. These free radicals act in various ways, e.g., they can react to form crosslinks, further breakage of PE chains, and to react with diffused oxygen with the polyethylene matrix following the well-established oxidation chain reactions of polyethylene [ 39 , 40 , 41 , 42 , 43 ]. Furthermore, the amount of free radicals is linearly correlated with the absorbed gamma dose, therefore, modifications in all above-mentioned regions, i.e., –CH 2 bending vibrations, absorption due –CH 2 units in amorphous region, –C=O absorptions, –CH 2 stretching vibrations, and peroxides bonded regions are higher for 65 kGy and 100 kGy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for irradiated samples, situation is quite different because samples suffer many chemical and physical changes because of radiation-induced free radicals. These free radicals act in various ways, e.g., they can react to form crosslinks, further breakage of PE chains, and to react with diffused oxygen with the polyethylene matrix following the well-established oxidation chain reactions of polyethylene [ 39 , 40 , 41 , 42 , 43 ]. Furthermore, the amount of free radicals is linearly correlated with the absorbed gamma dose, therefore, modifications in all above-mentioned regions, i.e., –CH 2 bending vibrations, absorption due –CH 2 units in amorphous region, –C=O absorptions, –CH 2 stretching vibrations, and peroxides bonded regions are higher for 65 kGy and 100 kGy.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, gamma rays are also responsible for enhancing the hydrogen adsorption capacity of MWCNTs and the amount of functional-groups attached to the surface of MWCNTs. This is because of an increase in imperfections at MWCNTs surface by gamma radiations [ 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33] As is well-known, complementary metal-oxide-semiconductor (CMOS) technology, which comprises both P-type and N-type TFTs working complementarily, is the most successful circuit style for modern ICs because of its low static power dissipation and high noise margin [34][35][36] and is thus preferred in low-power and robust paper-based electronics. Although many recent studies have shown that semiconducting single-walled carbon nanotubes (CNTs) are one of the ideal materials for achieving high-performance, flexible and radiation-tolerant CMOS ICs, [37][38][39][40][41][42][43][44] few works have fabricated CNT CMOS ICs on paper-based substrates, especially using E-mode CNT CMOS TFTs with low power consumption. Therefore, the fabrication of low-power-consumption CMOS ICs on paper substrates is famously challenging, which has hindered the development of paper-based electronics.…”
Section: Research Articlementioning
confidence: 99%
“…Consequently, the impacts of experimental and environmental conditions on the temporal evolution of defect populations (via optoelectronic properties) are still poorly understood. Over the last decade or so, there have been studies of the radiation hardness of carbon nanotube transistors and electronic circuits, in the context of extraterrestrial exposure to high energy radiation, which point to resistance of the carbon nanotube networks to chemical damage, due to the robustness of the C–C bonds to protons or γ rays. Similarly, the prevailing opinion in the community is that CNTs are inherently photostable when photoexcited in the visible and near-IR. , As such, when degradation of devices is observed, it has generally been attributed to other constituents in the device. , As an example, “photobleaching” of SWCNT emission intensity was observed for s-SWCNTs where O-related defects were created by ozonolysis, but the authors speculated that the photodegradation of surfactant micelles led to the creation of new exciton quenching sites . Flavel and Chen found recently that SWCNT/Nafion composite contacts enable high-efficiency silicon solar cells, but with poor long-term stability that the authors attributed to the hygroscopic nature of Nafion .…”
Section: Introductionmentioning
confidence: 99%